Evolution of the shut-off steps of vertebrate phototransduction. Issue 1 (10th January 2018) - Lamb, Trevor D.; Patel, Hardip R.; Chuah, Aaron; Hunt, David M.
Abstract : Abstract : Different isoforms of the genes involved in phototransduction are expressed in vertebrate rod and cone photoreceptors, providing a unique example of parallel evolution via gene duplication. In this study, we determine the molecular phylogeny of the proteins underlying the shut-off steps of phototransduction in the agnathan and jawed vertebrate lineages. For the G-protein receptor kinases (GRKs), the GRK1 and GRK7 divisions arose prior to the divergence of tunicates, with further expansion during the two rounds of whole-genome duplication (2R); subsequently, jawed and agnathan vertebrates retained different subsets of three isoforms of GRK. For the arrestins, gene expansion occurred during 2R. Importantly, both for GRKs and arrestins, the respective rod isoforms did not emerge until the second round of 2R, just prior to the separation of jawed and agnathan vertebrates. For the triplet of proteins mediating shut-off of the G-protein transducin, RGS9 diverged from RGS11, probably at the second round of 2R, whereas Gβ5 and R9AP appear not to have undergone 2R expansion. Overall, our analysis provides a description of the duplications and losses of phototransduction shut-off genes that occurred during the transition from a chordate with only cone-like photoreceptors to an ancestral vertebrate with both cone- and rod-like photoreceptors.